KONTAMINASI BAKTERI PADA SEMUT MONOMORIUM SP. (HYMENOPTERA: FORMICIDAE) YANG DITEMUKAN DI RUANG RAWAT INAP KELAS III RUMAH SAKIT â€œXâ€ KABUPATEN KENDAL - Lestari, Dwi Nikmah; Ginandjar, Praba; Hestiningsih, Retno (Fakultas Kesehatan Masyarakat, 2019)
Ants are one of the insects that are opportunist or adaptableÂ in various places, including hospitals. Ants that are famous as pest in hospital is Monomorium sp. In the United Kingdom it has been reported that the main problem caused by these ants are skin irritation and skin lesions that develop into infections, because of the presence of microorganisms carried by these ants. The purpose of this research is to determine the types of bacteria carried by Monomorium sp. in theÂ â€œXâ€ Hospital of Kendal district. Sampling is done by trapping with bait trap which was carried out in class III inpatient room at X Hospital of Kendal district. Identification of ants using the Key to Vietnamese literature Myrmicinae Genera and Key to Australian Genera of Myrmicinae. Three positive rooms were found in Monomorium sp. there are inpatient room of pediatric patients (30.8%), inpatient room of postpartum patients (46.1%) and inpatient room of patients in internal medicine 1 (23.1%). The bacteria found in Monomorium sp. were Escherichia coli, Staphylococcus sp. and Bacillus sp. An integrated ants control in hospital and socialization to patients, visitors or officers about the importance of preventing contact between body, food and drink with ants in the hospital is required to minimize their potential as vector of agent of diseases, especially bacteria.Â